Nationalism Transformation in Aceh - Effendi Hassan; Zulfiadi Ahmedy (POLITIK, 2015)
AbstrakNasionalisme adalah ideologi dasar bagi gerakan perlawanan terhadap kolonialisme di dunia. Ideologi ini cepat berkembang antara sesama negara di dunia dalam mempertahankan diri dari kolonialisme dan pengaruh dari luar negeri. Di Indonesia, nasionalisme menjadi kesatuan bangsa-bangsa di Nusantara dalam melawan penjajahan Belanda. Namun, setelah Indonesia merdeka, justru menjadi perusak nasionalisme itu sendiri. Kekecewaan kaum nasionalis menjadi awal gerakan perlawanan terhadap Indonesia. Kemudian pertentangan kaum nasionalis kian meluas dan menghancurkan landasan nasionalisme yang telah tumbuh kuat dan menjadi ancaman bagi nasionalisme Indonesia. Di Aceh, pergolakan yang melibatkan nasionalisme sebagai masalah dasar dapat meruntuhkan semangat nasionalisme Indonesia di pikiran rakyat Aceh, sehingga akan melahirkan etnonasionalisme yang dapat membatasi wacana nasionalisme, serta memperkuat semangat perlawanan untuk memisahkan diri dari Indonesia.Kata kunci: Transformasi, Nasionalisme, Aceh AbstractNationalism becomes a basic ideology of the resistance movement against colonialism whichvexists in the world. This ideology is able in bounding nations accross the world to defend themselves from colonialism and influences which come from outside the nations. In Indonesia, nasionalism becomes a unity of the nation in the archipelago against the Dutch colonialism. However, after Indonesia’s independence, nationalism becomes a destroyer of the nationalism itself, nationalist’s disappointment becomes a beginning of resistence movement against Indonesia. Later on the nationalist’s counterwork expanded broadly and destroyed the current nationalism foundation which had been grown strongly, and it grows as the menace for the nationalism of Indonesia. In Aceh, the upheaval involves nationalism as a basic problem that may collapse the spirit of Indonesia nationalism which exists on Acehnese’s mind, and it is switched with ethnonationalism which limits nationalism discourse as well as more reinforce the spirit of resistance in order to seperate itself away from Indonesia.Keywords: Transformation, Nationalism, Aceh